Interest and limits of the HFT method to evaluate the energy value of compound feeds for small ruminants - Giger-Reverdin S.; Maaroufi C.; Bontems V.; Jousse C. (Sheep and goat nutrition: Intake, digestion, quality of products and rangelands, 2000)
In vivo organic matter digestibility (OMD) of 34 compound feeds was measured on dairy goats or on male castrated sheep. In vitro gas production of these 34 compound feeds was calculated from gas production of ingredients. OMD was well predicted by gas production, but the coefficients of this new equation differed from those proposed previously by Menke and Steingass. The coefficients of the equation predicting OMD from gas production and protein content differed also from those of Menke and Steingass. The most precise prediction included gas production, crude protein and lignin percentages. This model was not previously tested. Residuals of the Menke and Steingass equations applied to our data are correlated to the percentage of cereals in the compound feeds, which limits their use. This was not the case for the equations proposed in this paper. These equations allowed to predict with a high degree of precision and close to what was observed in vivo the OMD of compound feeds for ruminants, and thus their energy value.
8. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1998/09/03-05, Grignon (France)